Study of Feasibility of Partial Replacement of Pozzolanic Materials for Cement In Recycled Aggregate Concrete - Tamboli, Nilofar R.; Malave , Pooja A.; Gawade , Aditya B.; Kalasakar , Shubhangi S.; Pawar , Suhas (International Journal of Scientific Research in Civil Engineering, 2020)
In developing country like India infrastructures play an important role in achieving rapid and continuous growth of country. Concrete is major material required for construction of infrastructure. The main gradient of concrete is aggregates and cement. Aggregate used in concrete are obtained by crushing or breaking a large rock in required size. But natural aggregates are becoming increasingly scarce and its shipment is becoming more difficult. The cement is manufactured through a closely controlled chemical combination of calcium, silicon, aluminium, iron clay and other ingredients. Hence to reduce use of natural rock, recycled aggregates and pozzolanic materials are currently used in concrete surface applications, but there is need for some additional work to determine the feasibility of utilizing this industrial by-product more wisely as a replacement for cement in a conventional concrete mixture. The primary aim of this project is to evaluate the strength of concrete made with recycled aggregates and pozzolanic materials. This study present result of experimental investigations carried out to evaluate effect of partially replacement of cement by pozzolanic materials on various concrete properties. In the present study M40 grade of concrete having three cubes for each mix tested for their 7 days and 28 days compressive strength were determined adopting conventional testing procedure. Ingredients used in this project for making concrete cubes are cement, sand, recycled, aggregates and pozzolanic materials as partial replacement of cement and water is used for making mixture of this ingredients. All tests are taken which is necessary before they are used for making concrete. Keyword: Pozzolanic, Compressive strength, concrete.